Meningkatkan Hasil Belajar PAI melalui Model Pembelajaran Contextual Teaching and Learning Tipe Konstruktivis pada Siswa Kelas XI MIA I SMA Negeri 3 Konawe Selatan - Kharis Sulaiman Hasri Nurhidayat (Al-Riwayah : Jurnal Kependidikan, 2019)
The purpose of this study was to determine the improvement of student learning outcomes through the learning model of the Contextual Teaching and Learning of Constructivist Type in class XI MIA I South Konawe 3 High School, Laeya sub-district, South Konawe district. The results of the study indicate that the learning model of Contextual Teaching and Constructivist Learning Types can improve student learning outcomes. The implementation of the first cycle obtained an average value of student learning outcomes of 74.88 or 76% of students who obtained a value of ≥65, so that it was continued in the second cycle. The implementation of the second cycle was obtained by the average learning outcomes of students getting a value of 77 or 84% of students who obtained a value of ≥65. By looking at the test results in the second cycle, this study was carried out only until the second cycle because the indicators of success of this study were achieved and improved learning outcomes in each cycle.